2019
DOI: 10.5662/wjm.v9.i3.32
|View full text |Cite
|
Sign up to set email alerts
|

DNA extraction from archived hematoxylin and eosin-stained tissue slides for downstream molecular analysis

Abstract: BACKGROUNDHistopathologically stained archived tissue slides are stored in hospital archives for years to decades. They are the largest available source of biological materials and are a potentially useful resource that can be used for retrospective epidemiological studies. DNA recovered from the slides can be used for several downstream molecular processes including polymerase chain reaction, single nucleotide polymorphism analysis, and whole genome sequencing. The DNA from these slides can be utilized to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…G2438, https://collections.qm.qld.gov.au/objects/PR121/theileria-peramelis ). While extraction of genetic material from tissue slides has been described ( Ramesh et al., 2019 ), the non-destructive sampling of blood smears from type-specimens is currently not practical. Therefore, pending further evidence, it is likely the sequences identified in the present study can be assigned to T. peramelis Mackerras, 1959 , and the host record expanded to include black rats ( R. rattus ).…”
Section: Discussionmentioning
confidence: 99%
“…G2438, https://collections.qm.qld.gov.au/objects/PR121/theileria-peramelis ). While extraction of genetic material from tissue slides has been described ( Ramesh et al., 2019 ), the non-destructive sampling of blood smears from type-specimens is currently not practical. Therefore, pending further evidence, it is likely the sequences identified in the present study can be assigned to T. peramelis Mackerras, 1959 , and the host record expanded to include black rats ( R. rattus ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it induces protein-nucleic acid crosslinking. Crosslinking impedes the separation of the DNA from histones, impairing the quantity as well as the quality of the extracted DNA (Ramesh et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For the mutational analysis, DNA was isolated from slides that were prepared from FFPE blocks. A handful of studies have demonstrated the feasibility of this method as an alternative to DNA isolation directly from FFPE, which is most commonly used (Ramesh et al 2019). This approach was successful in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequentemente, as amostras retiradas foram desparafinizadas por lavagens consecutivas com xileno, etanol a 100%, etanol a 70% e água destilada durante 10 minutos para cada solução. Finalmente, as amostras foram deixadas a secar durante 20 minutos à temperatura ambiente e foram colocadas em tubos PCR de 200 µl e depois para a sua conservação em congelação a -20 °C até à sua análise 10,11 (ver abaixo).…”
Section: Diagnóstico Por Pcr De Infecção Por Trypanosoma Cruziunclassified